Cardiac Niche Influences the Direct Reprogramming of Canine Fibroblasts into Cardiomyocyte-Like Cells - Giacomo Palazzolo; Mattia Quattrocelli; Jaan Toelen; Roberto Dominici; Luigi Anastasia; Guido Tettamenti; Inès Barthelemy; Stephane Blot; Rik Gijsbers; Marco Cassano; Maurilio Sampaolesi (Stem Cells International)
The Duchenne and Becker muscular dystrophies are caused by mutation of dystrophin gene and primarily affect skeletal and cardiac muscles. Cardiac involvement in dystrophic GRMD dogs has been demonstrated by electrocardiographic studies with the onset of a progressive cardiomyopathy similar to the cardiac disease in DMD patients. In this respect, GRMD is a useful model to explore cardiac and skeletal muscle pathogenesis and for developing new therapeutic protocols. Here we describe a protocol to convert GRMD canine fibroblasts isolated from heart and skin into induced cardiac-like myocytes (ciCLMs). We used a mix of transcription factors (GATA4, HAND2, TBX5, and MEF2C), known to be able to differentiate mouse and human somatic cells into ciCLMs. Exogenous gene expression was obtained using four lentiviral vectors carrying transcription factor genes and different resistance genes. Our data demonstrate a direct switch from fibroblast into ciCLMs with no activation of early cardiac genes. ciCLMs were unable to contract spontaneously, suggesting, differently from mouse and human cells, an incomplete differentiation process. However, when transplanted in neonatal hearts of SCID/Beige mice, ciCLMs participate in cardiac myogenesis.